Novel neurofibromatosis type 2 mutation presenting with status epilepticus. Issue 1 (March 2014) - DiFrancesco, Jacopo C.; Sestini, Roberta; Cossu, Federica; Bolognesi, Martino; Sala, Elena; Mariani, Silvana; Saracchi, Enrico; Papi, Laura; Ferrarese, Carlo
<x xml:space="preserve">Abstract</x> Neurofibromatosis type 2 (NF2) is a dominantly inherited syndrome caused by mutations of the tumour‐suppressor NF2, which encodes the merlin protein. Mutations are associated with a predisposition to development of benign tumours in the central nervous system. Even though cerebral cortical lesions are frequently associated with seizures, epilepsy is rarely described in NF2. Here, we describe an adult case of NF2 in which the onset of symptoms was characterised by status epilepticus. In this patient, we identified the novel c.428_430delCTTdel mutation in NF2, involving the amino‐terminal FERM domain, which is fundamental for the correct tumour suppressor function of the protein. Bioinformatic analyses revealed an important structural perturbation of the FERM domain, with a predicted impairment of the anti‐tumour activity.